PENGARUH PENDEKATAN OPEN ENDED TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 1 LEMBO PADA MATERI SEGITIGA - Kambodji, Axellino; Sumarauw, Sylvia J. A.; Regar, Vivian E. (SOSCIED, 2025)
The objective of this study was to assess the impact of the Open Ended approach on the mathematics learning outcomes of seventh-grade students at SMP Negeri 1 Lembo, specifically regarding Triangle Material. This research is classified as pseudo-experimental, utilizing a quantitative approach and employing a Non-equivalent Control Group Design. Class VII B served as the experimental class with 20 students, while class VII C acted as the control class, also comprising 20 students. The data collected for this study were analyzed using Microsoft Excel with a t-test, revealing a tcount value of 3.39484, which is greater than the ttable value of 2.02439 at a significance level of Î± = 0.05. Consequently, the research hypothesis was accepted. The findings of this study indicate that the Open Ended approach significantly influences the learning outcomes of seventh-grade students at SMP Negeri 1 Lembo in relation to triangle material.